Hubungan antara Pengetahuan dengan Sikap Masyarakat dalam Mencegah Leptospirosis di Desa Pabelan Kecamatan Kartasura Kabupaten Sukoharjo - Fuadi, Fatkhurrohman Ilham, Agus Sudaryanto, S.Kep., Ns., M.Kes, Endang Zulaicha S., S. Kep., M.Kep (2016)
Leptospirosis is a zoonotic disease caused by the bacteria leptospira and has a significant impact on health in many parts of the world sub-tropical and tropical climates. Reservoir or the main disseminators of leptospira are mice. Infected rat urine leptospira carried by the flood and can enter the human body through broken skin and mucous membranes. All cases are mild leptospirosis (anikterik) can recover completely, in contrast with severe leptospirosis (jaundice) which has a number of high Case Fatality Rate, between 5% -40%. Prevention is one way to reduce the number of leptospirosis cases, of which is to foster an attitude and a good knowledge of leptospirosis. The purpose of this study was to determine the relationship between knowledge and attitude of the public in preventing leptospirosis in Pabelan Village, District Kartasura, Sukoharjo. This is quantitative research with cross sectional design. The sampling technique used accidental sampling at a meeting of RT and the PKK with the number of 212 respondents aged 18-45 years. The instruments of measuring data was quesioner about knowledge and attitude Measuring instruments used in the form of knowledge and attitude questionnaire. Data analysis used Spearman Rank (Rho). The majority of respondents were female (62.3%), in the 39-45 age range (43.9%) and elementary education history pass as many as 74 people (34.9%). Knowledge of respondents categorized as less (53.3%), but 80.7% of the respondents have a good attitude. The analysis results obtained p value 0.901 (p> 0.05) so that Ha Ho is rejected and accepted. The conclusion is there is no significant relationship between knowledge with the attitude of the community in preventing leptospirosis in Pabelan Village, District Kartasura, Sukoharjo. The correlation coefficient is -0.009 which indicates the direction a negative correlation. Keywords: knowledge, leptospirosis, leptospira, attitude, prevention of leptospirosis.